Population dynamics and demographic history of Eurasian collared lemmings - Edana Lord; Aurelio Marangoni; Mateusz Baca; Danijela Popović; Anna V. Goropashnaya; John R. Stewart; Monika V. Knul; Pierre Noiret; Mietje Germonpré; Elodie-Laure Jimenez; Natalia I. Abramson; Sergey Vartanyan; et al. (BMC Ecology and Evolution, 2022)
Abstract Background Ancient DNA studies suggest that Late Pleistocene climatic changes had a significant effect on population dynamics in Arctic species. The Eurasian collared lemming (Dicrostonyx torquatus) is a keystone species in the Arctic ecosystem. Earlier studies have indicated that past climatic fluctuations were important drivers of past population dynamics in this species. Results Here, we analysed 59 ancient and 54 modern mitogenomes from across Eurasia, along with one modern nuclear genome. Our results suggest population growth and genetic diversification during the early Late Pleistocene, implying that collared lemmings may have experienced a genetic bottleneck during the warm Eemian interglacial. Furthermore, we find multiple temporally structured mitogenome clades during the Late Pleistocene, consistent with earlier results suggesting a dynamic late glacial population history. Finally, we identify a population in northeastern Siberia that maintained genetic diversity and a constant population size at the end of the Pleistocene, suggesting suitable conditions for collared lemmings in this region during the increasing temperatures associated with the onset of the Holocene. Conclusions This study highlights an influence of past warming, in particular the Eemian interglacial, on the evolutionary history of the collared lemming, along with spatiotemporal population structuring throughout the Late Pleistocene.